Intergenerational social mobility of cohorts born from 1951 to 1980 in Finland - Ruggera, Lucia; Kilpi-Jakonen, Elina; Erola, Jani (SAGE Publications Ltd, 2025)
Theories of change in social class mobility present contrasting expectations of either change or persistence in mobility as societies develop. This article examines intergenerational social class mobility for cohorts born from 1951 to 1980 in Finland. We analyse change across cohorts in the main association between social origins and destinations and the intervening associations between origins and education and education and destinations. We investigate how the association between education and destinations differs by origins and by education levels to gain a more complete picture of how meritocratic fairness has changed. We employ full population census and register data, using multiplicative log-linear models. The results suggest variations in the association between social origins and destinations over cohorts, which disappear when considering this association net of education. Educational inequalities have decreased for both men and women, whereas returns to education decreased for men but remained stable for women. Behind these relatively straightforward results is more complexity when considering how origins – also across cohorts – moderate class returns to education. These results suggest that the labour market is becoming more similar for individuals at different levels of education or coming from different social classes.